Effect of Rapid Thermal Annealing on the Emission Properties in InGaAsSb/AlGaAsSb Multiple Quantum Wells. Issue 6 (2nd May 2021) - Jia, Huimin; Wang, Dengkui; Azad, Fahad; Tang, Jilong; Shen, Lin; Hou, Xiaobing; Fang, Xuan; Fang, Dan; Lin, Fengyuan; Li, Kexue; Su, Shichen; Ma, Xiaohui; et al.
Abstract : An effect of rapid thermal annealing (RTA) on emission properties of InGaAsSb/AlGaAsSb multiple quantum wells (MQWs) grown by molecular‐beam epitaxy is systematically investigated by photoluminescence (PL) spectra. The emission from free‐exciton and localized carriers is confirmed in as‐grown InGaAsSb/AlGaAsSb MQWs using temperature and excitation power‐dependent PL spectra. The results of RTA for different times at a fixed temperature of 350 °C are analyzed. The PL intensity of InGaAsSb/AlGaAsSb MQWs is increased after an RTA process, and the peak position is slightly blueshifted at 300 K. Low‐temperature PL spectra show improved emission of free‐exciton and deteriorated localized carriers recombination at an annealing time of 60 s. Double crystal X‐ray diffraction (DCXRD) measurements are also carried out to study the crystalline quality before and after annealing. These results indicate that a suitable RTA treatment is effective in reducing the densities of nonradiative recombination centers, which implies an improved optical property and crystalline quality of quantum well structures. This study provides valuable understanding of recombination processes and improvement of optical properties by RTA treatment in InGaAsSb/AlGaAsSb MQWs. Abstract : Localized carriers emission is confirmed in InGaAsSb/AlGaAsSb multiple quantum wells (MQWs) using temperature and excitation power‐dependent photoluminescence (PL) spectroscopy. Rapid thermal annealing (RTA) is carried for different times under a temperature of 350 °C. Low‐temperature PL and X‐ray diffraction (XRD) results show that a suitable RTA treatment decreases the localized carriers emission, which implies an improved optical property and crystalline quality of quantum well structures.